Evaluate the physicochemical parameters and phytochemical screening of Kodiveli chooranum - Varuna, V.; Thayalin, T.; Velayuthamurty, K. (University of jaffna, 2025)
Medicinal plants are vital in traditional medicine due to their secondary metabolites. Standardization is crucial for ensuring the quality, efficacy, and safety of herbal drugs. This study evaluated the physicochemical parameters and phytochemical composition of Kodiveli chooranum (KC), a polyherbal formulation used in Siddha Medicine for various skin disorders. Physicochemical parameters, including ash values, pH, loss on drying, total solids, extractive values, swelling index, heavy metal content, and microbial load, were determined according to procedures [1, 2]. Phytochemical screening was performed on aqueous and methanolic extracts of KC and its constituent plants. The total ash content of KC was 6.29 ± 0.09%, with an acid-insoluble ash of 1.66 ± 0.22%. The pH was 6.04 ± 0.08, and the loss on drying was 6.66 ± 0.84%. The total solid content of the aqueous extract was 8.93 ± 0.22%, with alcohol-soluble and water-soluble extractive values of 4.83 ± 0.12% and 9.37 ± 1.36%, respectively. The swelling index was 30.35%. Heavy metal analysis revealed lead at 0.6 mg/Kg, while arsenic, cadmium, and mercury were below detectable limits. Microbial load testing showed a total bacterial count of 1.54 x 105 CFU/g and a fungal count of 6.00 x 102 CFU/g. Phytochemical screening of KC extracts indicated the presence of all tested phytochemicals except flavonoids. These findings suggest that KC's physicochemical parameters are within acceptable limits based on WHO guidelines. The presence of diverse phytochemicals supports its potential use in treating skin disorders. Further studies are warranted to evaluate the antimicrobial properties and to determine the minimum inhibitory concentration of KC to validate its therapeutic efficacy.
Keywords: Kodiveli chooranum; Standardization; Phytochemical screening